Interfaces in metal halide perovskite photovoltaics - Oliver, R (2022)
Metal halide perovskite (MHP) semiconductors are an extremely promising class of materials for photovoltaic (PV) applications. The outstanding optoelectronic properties of MHPs and their relative ease of manufacture have caused much excitement in the PV research and industrial communities alike. In turn, the solar-to-electrical power conversion efficiencies of PV devices based on MHPs have continued to soar over the past decade. Typically, and throughout this thesis, these are hybrid organic-inorganic semiconductors which combine many of the best aspects of both inorganic and organic semiconductors. Namely, their high charge-carrier mobility, long charge-carrier lifetimes and diffusion lengths are typical of inorganic semiconductors, whereas their low temperature processability and tunable optoelectronic properties are more typical of organic semiconductors.